Odpowiedzi

Najlepsza Odpowiedź!
2009-10-07T15:20:09+02:00
2x(x-1)+4=2(x-1) do potęgi 2
2x²-2x+4=2(x²-2x+1)
2x²-2x+4=2x²-4x+2
2x²-2x²-2x+4x+4-2=0
2x+2=0
2x=-2/:2
x=-1
4 2 4
2009-10-07T15:25:16+02:00
2x(x-1)+4=2(x-1) do potęgi 2= 2xkwadrat-2x+4=2(x-1)(x-1)=2xkwadrat-2x+4=(2x-2)(x-1)=2xkwadrat-2x+4=2xkwadrat-2x-2x+2=2xkwadrat-2xkw.-2xkw.+2x+2x=2-4= 2x=-2/:2 x=-1
1 5 1
2009-10-07T16:40:28+02:00
2x(x-1)+4=2(x-1) do potęgi 2= 2xkwadrat-2x+4=2(x-1)(x-1)=2xkwadrat-2x+4=(2x-2)(x-1)=2xkwadrat-2x+4=2xkwadrat-2x-2x+2=2xkwadrat-2xkwadrat-2xkwadrat+2x+2x=2-4= 2x=-2/:2 x=-1